(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
This experiment was designed in the field of animal production of the Technical College / Al-Musayyib to study the effect of adding Mentha pulegium and thymus Vulgaris powder and their mixture to the diet of broiler on the performance and some blood parameters. In this experiment, 96 chick strain Ross308 one day old was used with avarge weight of 40 g / chick distributed on the basis of a completely random design on four treatments, each treatment contained two replicates, 24 chicks / treatment. Treatments were, first treatment (control diet that does not contain any addition), the second treatment (control diet + Mentha Pulegium powder 0.6%), the third treatment (control diet + Thymus Vulgaris powder 0.6%) and the fourth treatment (control diet + mixture of Mentha Pulegium and Thymus Vulgaris powder 0.6% ). The results of the experiment showed significant differences (p£0.05)in the final weight of the fourth and second treatment respectively compared with the other treatments, it also the results of statistical analysis showed the presence of significant differences (p£0.05) in the rate of feed intake that was in favor of the fourth treatment that was less consumed to diet, while the control treatment had consumption of feed intake more than other treatments. The results of the experiment also showed the presence of a food conversion factor with significant differences (p£0.05)in favor of the fourth treatment. The dress weight of the fourth treatment was Higher than other treatments of the experiment.